The association between history of traumatic events and health-related quality of life among lung cancer patients. Issue 5 (2nd September 2020) - Bayley-Veloso, René; Szabo, Yvette Z.; Cash, Elizabeth; Zimmaro, Lauren; Siwik, Chelsea; Kloecker, Goetz; Salmon, Paul; van der Gryp, Kathleen; Sephton, Sandra E.
Abstract: Purpose: Promoting health-related quality of life (HRQOL) is a primary goal of lung cancer treatment. Trauma history and distress can negatively impact HRQOL. Design: A cross-sectional design examined the associations of trauma history, cancer-specific distress, and HRQOL. Sample/Method: Sixty lung cancer patients completed questionnaires on trauma history including the number and severity of traumatic events experienced. Cancer-specific distress, HRQOL, and depression were also reported. Findings: As hypothesized, trauma history and cancer-specific distress were negatively associated with HRQOL (all r's > −.27). Depression emerged as a confound in the association between cancer-specific distress and HRQOL. Conclusions: Retrospectively-reported trauma was linked with poorer HRQOL in lung cancer patients. Implications: Interventions aimed at improving lung cancer patients' HRQOL should consider the possible role of trauma history (both frequency and distress).